Inhibition of Ongoing Influenza A Virus Replication Reveals Different Mechanisms of RIG-I Activation - Liu, GuanQun (J Virol, 2019)
Pattern recognition receptors provide essential nonself immune surveillance within distinct cellular compartments. Retinoic acid-inducible gene I (RIG-I) is one of the primary cytosolic RNA sensors, with an emerging role in the nucleus. It is involved in the spatiotemporal sensing of influenza A virus (IAV) replication, leading to the induction of type I interferons (IFNs). Nonetheless, the physiological viral ligands activating RIG-I during IAV infection remain underexplored. Other than full-length viral genomes, cellular constraints that impede ongoing viral replication likely potentiate an erroneous viral polymerase generating aberrant viral RNA species with RIG-I-activating potential. Here, we investigate the origins of RIG-I-activating viral RNA under two such constraints. Using chemical inhibitors that inhibit continuous viral protein synthesis, we identify the incoming, but not de novo-synthesized, viral defective interfering (DI) genomes contributing to RIG-I activation. In comparison, deprivation of viral nucleoprotein (NP), the key RNA chain elongation factor for the viral polymerase, leads to the production of aberrant viral RNA species activating RIG-I; however, their nature is likely to be distinct from that of DI RNA. Moreover, RIG-I activation in response to NP deprivation is not adversely affected by expression of the nuclear export protein (NEP), which diminishes the generation of a major subset of aberrant viral RNA but facilitates the accumulation of small viral RNA (svRNA). Overall, our results indicate the existence of fundamentally different mechanisms of RIG-I activation under cellular constraints that impede ongoing IAV replication. IMPORTANCE The induction of an IFN response by IAV is mainly mediated by the RNA sensor RIG-I. The physiological RIG-I ligands produced during IAV infection are not fully elucidated. Cellular constraints leading to the inhibition of ongoing viral replication likely potentiate an erroneous viral polymerase producing aberrant viral RNA species activating RIG-I. Here, we demonstrate that RIG-I activation during chemical inhibition of continuous viral protein synthesis is attributable to the incoming DI genomes. Erroneous viral replication driven by NP deprivation promotes the generation of RIG-I-activating aberrant viral RNA, but their nature is likely to be distinct from that of DI RNA. Our results thus reveal distinct mechanisms of RIG-I activation by IAV under cellular constraints impeding ongoing viral replication. A better understanding of RIG-I sensing of IAV infection provides insight into the development of novel interventions to combat influenza virus infection.